2016
DOI: 10.1016/j.jenvman.2016.07.092
|View full text |Cite
|
Sign up to set email alerts
|

Activating social strategies: Face-to-face interaction in technology-mediated citizen science

Abstract: The use of crowds in research activities by public and private organizations is growing under different forms. Citizen science is a popular means of engaging the general public in research activities led by professional scientists. By involving a large number of amateur scientists, citizen science enables distributed data collection and analysis on a scale that would be otherwise difficult and costly to achieve. While advancements in information technology in the past few decades have fostered the growth of ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 79 publications
2
69
0
3
Order By: Relevance
“…The citizens should be actively involved in these collaborative interactions, because users' appreciation of, and commitment to, urban change is almost always essential to smart initiatives' success [63]. Effective collaborative interactions between startups/entrepreneurs, scientists and citizens [69][70][71] allow for viable, distributed experimentation on concrete city-level needs [64]. Universities are expected to support and/or directly participate in these networks, thus activating the so-called triple helix (university, industry and government) [72].…”
Section: The Smart City As An Organizational Fieldmentioning
confidence: 99%
“…The citizens should be actively involved in these collaborative interactions, because users' appreciation of, and commitment to, urban change is almost always essential to smart initiatives' success [63]. Effective collaborative interactions between startups/entrepreneurs, scientists and citizens [69][70][71] allow for viable, distributed experimentation on concrete city-level needs [64]. Universities are expected to support and/or directly participate in these networks, thus activating the so-called triple helix (university, industry and government) [72].…”
Section: The Smart City As An Organizational Fieldmentioning
confidence: 99%
“…The results from panel analysis and sample selection model are consistent [22,23]. Therefore, we could conclude that the sample size used in the regression analysis is large enough.…”
Section: The Romanian Research System-between Communism Ruins and Glomentioning
confidence: 53%
“…We found that the availability of a web-system encouraged a large and diverse population of volunteers to report observations and to stay retained as observers. In CA we observed a gradual downward trend in rates of observation, which could be related to a persistent drought in California (i.e., causing declines in wildlife) or the level of engagement with volunteers, such as with face-to-face interactions, which are important for volunteer engagement (Cappa et al, 2016). We also found that the rates of identification-accuracy were high at the species level, which may be related to the high rate of involvement of professional scientists in our systems.…”
Section: Volunteer Scientistsmentioning
confidence: 88%